The Effects of Genetic Background for Diurnal Preference on Sleep Development in Early Childhood - Morales-Muñoz I (Dove Medical Press, 2021)
Isabel Morales-Muñoz,1,2 Katri Kantojärvi,1,3 Veli-Matti Uhre,1 Outi Saarenpää-Heikkilä,4,5 Anneli Kylliäinen,6 Pirjo Pölkki,7 Sari-Leena Himanen,8,9 Linnea Karlsson,10– 12 Hasse Karlsson,10– 12 E Juulia Paavonen,1,13 Tiina Paunio1,3 1Department of Public Health Solutions, Finnish Institute for Health and Welfare, Helsinki, Finland; 2Institute for Mental Health, School of Psychology, University of Birmingham, Birmingham, UK; 3Department of Psychiatry and SleepWell Research Program, Faculty of Medicine, University of Helsinki and Helsinki University Central Hospital, Helsinki, Finland; 4Pediatric Clinic, Tampere University Hospital, Tampere, Finland; 5Tampere Centre for Child Health Research, University of Tampere and Tampere University Hospital, Tampere, Finland; 6Psychology, Faculty of Social Sciences, Tampere University, Tampere, Finland; 7Department of Social Sciences, University of Eastern Finland, Kuopio, Finland; 8Department of Clinical Neurophysiology, Tampere University Hospital, Medical Imaging Centre and Hospital Pharmacy, Pirkanmaa Hospital District, Tampere, Finland; 9Faculty of Medicine and Health Technology, Tampere University, Tampere, Finland; 10The FinnBrain Birth Cohort Study, Turku Brain and Mind Center, Department of Clinical Medicine, University of Turku, Turku, Finland; 11Centre for Population Health Research, Turku University Hospital and University of Turku, Turku, Finland; 12Department of Psychiatry, University of Turku and Turku University Hospital, Turku, Finland; 13Pediatric Research Center, Child Psychiatry, University of Helsinki and Helsinki University Hospital, Helsinki, FinlandCorrespondence: Isabel Morales-Muñoz Tel +358 29 524 6000Email isabel.morales@thl.fiTiina Paunio Tel +358 29 410 2941Email tiina.paunio@helsinki.fiPurpose: No previous research has examined the impact of the genetic background of diurnal preference on children´s sleep. Here, we examined the effects of genetic risk score for the liability of diurnal preference on sleep development in early childhood in two population-based cohorts from Finland.Participants and Methods: The primary sample (CHILD-SLEEP, CS) comprised 1420 infants (695 girls), and the replication sample (FinnBrain, FB; 962 girls) 2063 infants. Parent-reported sleep duration, sleep-onset latency and bedtime were assessed at three, eight, 18 and 24 months in CS, and at six, 12 and 24 months in FB. Actigraphy-based sleep latency and efficiency were measured in CS in 365 infants at eight months (168 girls), and in 197 infants at 24 months (82 girls). Mean standard scores for each sleep domain were calculated in both samples. Polygenic risk scores (PRS) were used to quantitate the genetic risk for eveningness (PRSBestFit) and morningness (PRS10kBest).Results: PRSBestFit associated with longer sleep-onset latency and later bedtime, and PRS10kBest related to shorter sleep-onset latency in CS. The link between genetic risk for diurnal preference and sleep-onset latency was replicated in FB, and meta-analysis resulted in associations (P< 0.0005) with both PRS-values (PRSBestFit: Z=3.55; and PRS10kBest: Z=− 3.68). Finally, PRSBestFit was related to actigraphy-based lower sleep efficiency and longer sleep latency at eight months.Conclusion: Genetic liability to diurnal preference for eveningness relates to longer sleep-onset during the first two years of life, and to objectively measured lowered sleep efficiency. These findings enhance our understanding on the biological factors affecting sleep development, and contribute to clarify the physiological sleep architecture in early childhood.Keywords: genetic risk, chronotype, sleep, early childhood, cohorts